SISTEM INFORMASI PENJUALAN PADA CV. DISTRIBUSINDO BINTANG - Syakban (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The aim of this research is; 1) To find out the Sales Information System on CV. Distribusi Bintang, 2) To design a Sales Information System at CV. Distribution of web-based Bintang. In making this model the researchers compiled using a data flow diagram which is a system design tool, while in the prototype development process using the waterfall method. Based on the results of the research, the author can draw a conclusion which includes the following; 1) Use of Sales Information System on CV. Distribusi Bintang is expected to help create accurate and effective Sales Information data, 2) With the information system, it is easy for CV. Distribution of Bintang for speeding up information in general and reducing errors, and 3) Sales Information System on CV. Distribusi Bintang which the author designed uses various web-based programming languages ​​consisting of; HTML, CSS, Jquery, JavaScript, JSON PHP, and for database processing the Structure Query Language (SQL) is used. The supporting software used is XAMPP version 5.6 (Support MySQLi), NotePad ++, and Google Chrome Browser.